Innovations in literacy professional learning strengthening equity, access, and sustainability - Brock, Cynthia H.; Hall, Leigh A.; Robertson, Dana A. (The Guilford Press, 2023)
"Professional learning (PL) opportunities are essential for PreK-12 literacy educators, but too often these efforts fail to help teachers develop and deeply engage with their work. This forward-looking book describes keys to providing effective, sustainable literacy PL that values teachers over test scores and capitalizes on social networks and communities. The volume presents case studies of transformational initiatives tailored to culturally and linguistically diverse populations of teachers and students, varying school resources, urban or rural settings, and other factors. Issues of access and equity are emphasized throughout the book's discussions of innovative in-person, hybrid, and remote PL models. The companion website features 11 brief videos in which chapter authors provide engaging commentary on their respective topics. "--Provided by publisher.